2018
DOI: 10.1001/jamaneurol.2018.1935
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Midlife Risk Factors and Late-Onset Epilepsy

Abstract: IMPORTANCE The incidence of epilepsy is higher in older age than at any other period of life. Stroke, dementia, and hypertension are associated with late-onset epilepsy; however, the role of other vascular and lifestyle factors remains unclear. OBJECTIVE To identify midlife vascular and lifestyle risk factors for late-onset epilepsy. DESIGN, SETTING, AND PARTICIPANTS The Atherosclerosis Risk in Communities (ARIC) study is a prospective cohort study of 15 792 participants followed up since 1987 to 1989 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 64 publications
6
70
1
Order By: Relevance
“…We previously found the incidence of LOE in ARIC participants to be 3.3 per 1,000 person-years, 13 somewhat higher than other recently reported incidences of 2.4-2.5 per 1,000 person-years 2,3 ; this may be due in part to the relatively high proportion of black participants (25% of ARIC participants) as the rate of LOE is known to be higher in black than in white individuals. 2,3,13 The strengths of this study are the longitudinal nature of comparison of white matter scores and later epilepsy, large size, and prospective nature. These strengths allow us to include and adjust for vascular and lifestyle risk factors in our models, which is of vital importance given the high association of hypertension and smoking with the imaging measures under study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…We previously found the incidence of LOE in ARIC participants to be 3.3 per 1,000 person-years, 13 somewhat higher than other recently reported incidences of 2.4-2.5 per 1,000 person-years 2,3 ; this may be due in part to the relatively high proportion of black participants (25% of ARIC participants) as the rate of LOE is known to be higher in black than in white individuals. 2,3,13 The strengths of this study are the longitudinal nature of comparison of white matter scores and later epilepsy, large size, and prospective nature. These strengths allow us to include and adjust for vascular and lifestyle risk factors in our models, which is of vital importance given the high association of hypertension and smoking with the imaging measures under study.…”
Section: Discussioncontrasting
confidence: 60%
“…We adjusted for hypertension, diabetes, smoking, and APOE e4 genotype in our models, and excluded participants with known dementia, to attempt to address these considerations. The degree of these structural findings adds additional risk of LOE beyond the known risk factors of hypertension, diabetes, smoking, and APOE e4, 13 which were included in our models. This may imply that there is heterogeneity in susceptibility to the effects of these vascular and lifestyle risk factors; further studies to develop prediction models to identify patients at risk for LOE should incorporate imaging findings as well as medical and social risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis is a chronic inflammatory disease of the arteries, it is principally a lipid-driven process initiated by the accumulation of lipoprotein particles and an inflammatory process in focal areas of arteries as well. [38] Recently, miR-146a was recognized as a potent regulator in many physiological and pathological processes, including immune function, inflammatory reaction, metabolism, oxidative stress, neurodegenerative, and cardiovascular diseases. [39] Recent studies have shown that miR-146a can regulate the synthetic phenotype and proliferation of vascular smooth muscle cells by targeting Krüppel-like factor 4.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of GABA and GABAergic interneurons in AD patients may lead to network hyperactivity, most commonly observed through seizures. ApoE4 carriers have a higher risk [132136] and earlier onset [137139] of developing idiopathic or secondary temporal lobe epilepsy. It is still unclear whether these patients demonstrate a higher risk for developing AD later in life, or if indeed the proportion of AD patients with concomitant epilepsy is enriched for apoE4 carriers.…”
Section: Introductionmentioning
confidence: 99%